Clinical value of ultrasonography in the evaluation of multiple organs in patients with hyperuricemia - GAO Ze-yan, LIU Xiao-yue, CHEN Li-meng, TAN Li, ZHANG Yi-xiu, LI Jian-chu, LYU Ke (Jichu yixue yu linchuang, 2020)
Objective To explore and evaluate the clinical value of color Doppler ultrasound in the evaluation of multiple organs in patients with hyperuricemia. Methods The research included 50 patients with newly diagnosed hyperuricemia who were admitted to Peking Union Medical College Hospital from July 2015 to May 2017. Serum uric acid (sUA) was recorded and color Doppler ultrasound was used to examine the bilateral first metatarsophalangeal joint, knee joint, kidney, carotid artery and liver in each patient. The potential correlation between sUA level and organ lesions were searched. The subjects were further divided into gouty arthritis (GA) group and asymptomatic chyperuricemia (AH) group. The multiple organ diseases were analyzed and compared. Statistical methods used in cluded chi-square test and Spearman correlation analysis. Results In the 50 patients with newly diagnosed hyperuricemia, the rate of joint lesions diagnosed by ultrasound was 56.0%; the rate of renal morphological changes was 72.0%; the rate of nonalcoholic fatty liver disease (NAFLD) was 64.0%, of which 59.4% was moderate to severe fatty liver, and the sUA level was positively correlated with the detection rate of NAFLD(P＜0.05),the detection rate of carotid atherosclerosis was 36.0%, and the level of sUA was positively correlated with the thickness of the common carotid artery (P＜0.05).The detection rate of two or more organ lesions in joint, kidney, liver and carotid artery was 80.0%, and the level of sUA was positively correlated with the detection rate of multiple organ lesions (P＜0.05). There was a significant difference in the detection rate of joint lesions and carotid atherosclerosis between the GA group and the AH group (P＜0.05). Conclusions Color Doppler ultrasound has certain clinical application value for early diagnosis, comprehensive evaluation of lesion progression and follow-up treatment of multiple organ lesions such as joint lesions and renal damage, nonalcoholic fatty liver and carotid atherosclerosis in patients with hyperuricemia.